Systematic Review of Spatial Planning and Marine Protected Areas: A Brazilian Perspective - Borges, Rebecca; Eyzaguirre, Indira; Barboza, Roberta Sá Leitão; Glaser, Marion (Frontiers in Marine Science, 2020)
Marine protected areas (MPAs) are essential to human well-being and usually part of spatial planning processes for managing coastal and marine areas. In Brazil, national-level spatial planning processes are still incipient. This article offers a systematic review through a comparative meta-analysis of the literature on MPAs and spatial planning based on the following questions: (I) What topics are investigated in spatial planning in MPAs worldwide? and (II) What are the advances and trends of these topics in Brazilian MPAs? Specific goals of this study are (I) to identify studies on Brazil; and (II) to compare and contrast these with studies performed elsewhere. The PRISMA report was used to select literature, with a focus on three spatial contexts (I) outside Brazil, analyzing studies from other countries; (II) in Brazil; and (III) a case study in Brazil that focuses on a sustainable-use area in northeastern Pará. Studies outside Brazil showed three major groups of themes: (I) planning and tools; (II) stakeholders; and (III) the ecology of non-human species. For the Brazilian context, studies were grouped into five major themes: (I) small-scale fishing practices and conflicts; (II) participation in protected areas; (III) technical aspects of the planning process, (IV) zoning; and (V) mapping. The local case study investigates socio-cultural sustainability and tourism. All identified studies relate to use, but have a greater focus on conservation and, especially abroad, on species and ecosystems. There are few reviews or comparative studies that could help to draw parallels between the different spatial planning settings. We conclude that synthesis work on spatial management strategies worldwide is needed, including the elaboration of frameworks to develop measures to address the widespread lack of data and spatial planning expertise. Collaborative networks of researchers and practitioners are needed for this. The novelty in our study is that it examines MPAs and spatial planning research at three spatial contexts with innovative methodologies to represent the current state of the spatial planning discourse in coastal and marine conservation.